The masterpiece [large type] - Rivers, Francine, 1947- (Thorndike Press, a part of Gale, a Cengage Company, 2018)
A successful LA artist, Roman Velasco appears to have everything he could possibly want--money, women, fame. Only Grace Moore, his reluctant, newly hired personal assistant, knows how little he truly has. The demons of Roman's past seem to echo through the halls of his empty mansion and out across his breathtaking Topanga Canyon view. But Grace doesn't know how her boss secretly wrestles with those demons: by tagging buildings as the Bird, a notorious but unidentified graffiti artist--an alter ego that could destroy his career and land him in prison. Like Roman, Grace is wrestling with ghosts and secrets of her own. After a disastrous marriage threw her life completely off course, she vowed never to let love steal her dreams again. But as she gets to know the enigmatic man behind the reputation, it's as if the jagged pieces of both of their pasts slowly begin to fit together . . . until something so unexpected happens that it changes the course of their relationship--and both their lives--forever.